Factor Analysis Of Stunting In CIlincing Public Health Center North Jakarta - Dahlan, Febry Mutiariami; Rohmawati, Alfi; Azzahroh, Putri (Rajaki of Tulip Medika Publisher, 2024)
Background: According to the Ministry of Health announced the results of the Indonesian Nutrition Status Survey (SSGI) at the BKKBN National Work Meeting, where the prevalence of stunting in Indonesia fell from 24.4% in 2021 to 21.6% in 2022. Therefore, the Government of Indonesia has a target for 2024 for the stunting rate to fall by around 14%. So that the reduction in stunting rates is still far from the target set by the Government. Indonesia is still experiencing problems in nutrition and child development. UNICEF suggests that around 80% of stunted children are found in 24 developing countries in Asia and Africa. Objective: This study aims to determine the factors related to stunting in Cilincing Public Health Center, North Jakarta in 2024. Methodology: Descriptive correlation research with cross sectional research design. Population 74 respondents aged 24-59 months with purposive sampling technique. The instrument used to perform variable calculations uses a questionnaire. Variables include Immunization History, Clean and Healthy Living Behavior (PHBS), Exclusive Breastfeeding History, Parenting Patterns and Diarrhea History. This data was analyzed using descriptive statistics chi-square. Results: The research results showed that the number of health workers who experienced stunting was greater (68.9%) compared to normal ones (31.1%). There is an average value of stunted toddlers with a complete immunization history (56,%), good PHBS (66,2%), exclusive breastfeeding history (77%). ), less good parenting patterns (51.4%) and history of diarrhea with Diarrhea (60.8%). So there is a significant relationship between the factors history of immunization, PHBS, Parenting Patterns and History of Diarrhea (p value <0.05). Conclusion and Suggestion: The availability of educational activities for the Cilincing Public Health Center in providing education on the knowledge of parents of toddlers about the factors of stunting incidence at the Cilincing District Public Health Center in 2024. The Puskesmas can provide education related to food diversity/variety, especially sources of animal protein.